Direct and quantitative evaluation of the human CYP3A4 contribution (fm) to drug clearance using the in vitro SILENSOMES model. (3rd July 2017) - Parmentier, Yannick; Pothier, Corinne; Delmas, Audrey; Caradec, Fabrice; Trancart, Marie-Michèle; Guillet, Fabrice; Bouaita, Belkacem; Chesne, Christophe; Brian Houston, J.; Walther, Bernard
Abstract: 1. Among the different in vitro studies recommended by the regulatory agencies, no gold-standard model can easily and directly measure the quantitative CYP450 contributions to drug biotransformation. In this article, we propose an original strategy, called Silensomes TM, to produce human liver microsomes silenced for one specific CYP450, thanks to specific mechanism-based inhibitors (MBI). 2. Using azamulin as a specific CYP3A4 MBI, we demonstrated the proof of concept that CYP3A4 can be totally, specifically (even against 3A5) and permanently (at least for six years) inhibited by our process. Thus, comparing clearance in control and CYP3A4-Silensomes TM, CYP3A4 contributions were determined for 11 CYP3A4 substrates which correlated with known in vivo contributions and revealed accuracy with less than 10% error. In comparison, contributions determined using recombinant human CYP450 (rhCYP450s) were less accurate (more than 10% error for 30% of the tested CYP3A4 substrates). 3. This easy and ready-to-use in vitro method combines the advantages of existing models (specificity of rhCYP450s and representativeness of HLM) without their drawbacks. The same strategy could be used to silence other major CYP450s one-by-one to provide a complete direct CYP450 quantitative phenotyping kit.